2022
DOI: 10.1021/acsomega.2c04669
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Mixed-Ligand H-Bonded Cu Coordination Polymer: Exploring the pH-Dependent High Photocatalytic Degradation of Rhodamine 6G, Methyl Violet, Crystal Violet, and Rose Bengal Dyes under Room Illumination

Abstract: A new mixed-ligand H-bonded coordination polymer {[Cu 2 (Or) 2 (Bimb) 3 ]•4H 2 O} n (KA@CP-S) has been prepared hydrothermally using basic copper carbonate with 1,4-bis[(1H-imidazol-1yl)methyl]benzene (Bimb) and potassium orotate (OrK) ligands. According to topological studies, KA@CP-S has a new topology with a three-connected uninodal net with point symbol (PS) {8 2 •12} 2 {8} 3 . The KA@CP-S was employed as a catalyst for screening of a series of harmful cationic, anionic, and neutral organic dyes in contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The degradation of antibiotics did not significantly diminish when AO was added to the reaction, suggesting that h + was not the major active species either. However, the degradation of antibiotics was significantly inhibited by the addition of BQ and TBA, indicating that O 2 ˙ − and ˙OH played a crucial role [ 58 , 59 , 60 , 61 ] in this photocatalytic reaction and confirming that ˙OH was the major active species, as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 77%
“…The degradation of antibiotics did not significantly diminish when AO was added to the reaction, suggesting that h + was not the major active species either. However, the degradation of antibiotics was significantly inhibited by the addition of BQ and TBA, indicating that O 2 ˙ − and ˙OH played a crucial role [ 58 , 59 , 60 , 61 ] in this photocatalytic reaction and confirming that ˙OH was the major active species, as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 77%
“…The significant degradation efficacy of BiGa x Fe 1– x O 3 was confirmed by the rapid removal of CV from the aqueous medium. The pH of the solution is a significant parameter in dye degradation because it can affect the surface charge of catalysts, the degradation tendency of the photocatalyst, due to its effect on functional groups, degree of ionization, and structure of dye molecules . The CV dye degradation behavior of BiGa x Fe 1– x O 3 was further investigated using an experimental setup with pH values ranging from 4 to 10 (Figures S11 and S12).…”
Section: Resultsmentioning
confidence: 99%
“…However, they noticed that in alkaline conditions, OH• combines with alkaline ions, reducing the quantity of reactive species and consequently slowing the rate at which CV degrades. A novel mixed-ligand hydrogen-bonded coordination polymer, {[Cu 2 (Or) 2 (Bimb) 3 ]Á4H 2 O} n (KA@CP-S), was developed using a hydrothermal technique by Somnath et al 169 At pH = 7.5, they found that 75.8% of CV was degraded, while at pH = 4, 10 and 12, they observed that 89.5%, 83% and 94% of CV was photocatalytically degraded, respectively. According to their interpretation, the complex's structural changes or interference from surrounding ionic species could result in a decrease in the degradation efficiency under extreme pH conditions.…”
Section: Effect Of Phmentioning
confidence: 99%